2021
DOI: 10.3390/cancers13215394
|View full text |Cite
|
Sign up to set email alerts
|

APC and TP53 Mutations Predict Cetuximab Sensitivity across Consensus Molecular Subtypes

Abstract: Recently, it was suggested that consensus molecular subtyping (CMS) may aide in predicting response to EGFR inhibitor (cetuximab) therapies. We recently identified that APC and TP53 as two tumor suppressor genes, when mutated, may enhance cetuximab sensitivity and may represent easily measured biomarkers in tumors or blood. Our study aimed to use APC and TP53 mutations (AP) to refine the CMS classification to better predict responses to cetuximab. In total, 433 CRC tumors were classified into CMS1-4 subtypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…In previous studies on somatic mutations in colon cancer, KRAS mutation is very common in colon cancer patients, and it reduces prognosis by inhibiting immune pathways [30]. As well-known tumor suppressor genes, TP53 and APC are important markers to guide the use of cetuximab in colon cancer [31]. This study found that TTN mutation still has an adverse effect on the prognosis of colon cancer, and the speci c mechanism remains to be further explored.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies on somatic mutations in colon cancer, KRAS mutation is very common in colon cancer patients, and it reduces prognosis by inhibiting immune pathways [30]. As well-known tumor suppressor genes, TP53 and APC are important markers to guide the use of cetuximab in colon cancer [31]. This study found that TTN mutation still has an adverse effect on the prognosis of colon cancer, and the speci c mechanism remains to be further explored.…”
Section: Discussionmentioning
confidence: 67%
“…48,[51][52][53][54] Another CRC study suggested that TP53 mutations are predictive for cetuximab sensitivity, especially for patients without KRAS mutations, 55 and proposed that TP53 genotyping could be useful in the clinic to help select CRC patients who are likely to benefit from cetuximabbased treatment. Thota et al (2021) found that APC and TP53 mutations can predict cetuximab sensitivity across consensus molecular subtypes, based on an analysis of multiple CRC tumor/ PDX/cell line datasets. 56 In our HNSCC PCT, all of the PDXs were wild-type KRAS, and we found that TP53 mutation was related to the sensitivity of cetuximab: the mutation rate of TP53 in the sensitive group was 100% but was only 62.5% in the intrinsic resistance group.…”
Section: Discussionmentioning
confidence: 99%
“…Thota et al (2021) found that APC and TP53 mutations can predict cetuximab sensitivity across consensus molecular subtypes, based on an analysis of multiple CRC tumor/ PDX/cell line datasets. 56 In our HNSCC PCT, all of the PDXs were wild-type KRAS, and we found that TP53 mutation was related to the sensitivity of cetuximab: the mutation rate of TP53 in the sensitive group was 100% but was only 62.5% in the intrinsic resistance group.…”
Section: Discussionmentioning
confidence: 99%
“…PP2AC expression accurately indicates therapeutic response to p38 inhibitor in CRC PDX 124 . APC and TP53 mutation as convenient biomarkers predicts the sensitivity to EGFR‐targeted therapies 125 . As the key markers are continuously screened out to evaluate the related treatment in CRC PDX models, more targeted drugs are also used more precisely.…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%
“…124 APC and TP53 mutation as convenient biomarkers predicts the sensitivity to EGFR-targeted therapies. 125 As the key markers are continuously screened out to evaluate the related treatment in CRC PDX models, more targeted drugs are also used more precisely. liver metastatic colonization by promoting nucleotide synthesis.…”
Section: Biomarker Discoverymentioning
confidence: 99%